Blockchain-based smart energy trading: Motivations and challenges - Amini A.; Jamil N.; Bohani F.A. (Compusoft, 2023)
The growing population and high demand of renewable energy leads to a decentralized solution to trade energy smartly. In an innovative energy market, consumers and prosumers are able to trade green energy locally and directly to balance the generation and consumption through decentralized community. In this paper, we present a comprehensive review of existing energy trading systems, their motivations and challenges. For this reason, new ICT technologies are investigated to consider their incredible affections on data transparency, energy trading and how energy consumer and producers are connected intelligently. The similarities, differences and challenges in different energy trading projects are identified. The comparison analysis leads us to analyze the future scenario of energy trading that can offer high level of data transparency, low trading cost and less trading time. 2020, National Institute of Science Communication and Information Resources (NISCAIR).